Theoretical foundations of uncertain event prognosis and predictive Bayesian Cramer-Rao bounds - Acuña Ureta, David E. (2020)
The reliability and operational continuity of systems have become increasingly important as technological progress translates into products that are gradually being incorporated and standardised in society. Some typical examples that can be named are the use of satellites for communications and location, biomedical engineering devices such as magnetic resonance, computers, machinery for manufacturing processes such as lathes or milling machines, vehicles, defense, among others.